Traffic characteristics of protected/permitted left-turn signal displays - Kacir, Kent C.; Fambro, Daniel B.; Noyce, David A. (My University, 2000)
At least four variations of the permitted indication in protected/permitted left-turn (PPLT) control have been developed in an attempt to improve the level of driver understanding and safety. These variations replace the green ball permitted indication with a flashing red ball, a flashing yellow ball, a flashing red arrow, or a flashing yellow arrow indication. In addition, the "Manual on Uniform Traffic Control Devices" allows several PPLT signal display arrangements. The variability in indication and arrangement has led to a myriad of PPLT displays throughout the United States. The level of driver understanding related to each PPLT display type, and the associated impact on traffic operations and safety, has not been quantified. A study was conducted to evaluate the operational characteristics associated with different PPLT signal displays. Specifically, the study quantified saturation flow rate, start-up lost time, response time, and follow-up headway associated with selected PPLT displays. No differences in saturation flow rate and start-up lost time were found due to the type of PPLT signal display. Saturation flow rates ranged from 1,770 to 2,400 vehicles per hour of green per lane and were related to differences in driver behavior between geographic locations. The variation in start-up lost time and response time between locations was primarily related to differences in phase sequence. The flashing red permitted indications were associated with the longest follow-up headway times, since drivers are required to stop before turning left with a flashing red permitted indication. The shortest follow-up headway was associated with the five-section cluster display using a green ball indication.
25 p. ; Prepared for the 79th Annual Meeting of the Transportation Research Board, Washington, D.C. January, 2000
Keywords: Exclusive permissive phasing; Traffic safety; Traffic signals; Manual on Uniform Traffic Control Devices (MUTCD); Left turns; Saturation flow; Reaction time; Comprehension